2004
DOI: 10.1507/endocrj.51.121
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine Levels in Hyperthyroid Patients

Abstract: Abstract. Hyperhomocysteinemia is a risk factor for premature atherosclerotic vascular diseases. It is known that plasma homocysteine levels are higher in hypothyroid patients compared to healthy subjects. The aim of our study was to assess plasma total homocysteine concentrations in hyperthyroid patients before and after treatment when euthyroid status was reached and compare them with control group. Thirteen hyperthyroid patients (age, 42.9 ± 15.6 year) and eleven healthy subjects (age, 39.9 ± 12.5 year) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
3
1
1
Order By: Relevance
“…Similar to hyperthyroidism in women, the results of this study suggest feline hyperthyroidism is not associated with a clinically important functional deficiency in cobalamin . However, the prevalence of hyperthyroid/hypocobalaminemia in this study is in contrast with the a recent retrospective study which reported a 40% prevalence in their population of hyperthyroid cats .…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Similar to hyperthyroidism in women, the results of this study suggest feline hyperthyroidism is not associated with a clinically important functional deficiency in cobalamin . However, the prevalence of hyperthyroid/hypocobalaminemia in this study is in contrast with the a recent retrospective study which reported a 40% prevalence in their population of hyperthyroid cats .…”
Section: Discussioncontrasting
confidence: 79%
“…In a recent study, a significant decrease in serum cobalamin concentrations were reported in hyperthyroid cats, however, MMA concentrations were not measured and the change in cobalamin status after treatment for hyperthyroidism was not assessed . Low serum cobalamin concentrations are also associated with hyperthyroidism in humans but are considered functionally unimportant as serum cobalamin levels rise significantly once euthyroid . Based on known differences in nutritional requirements as well as a much higher cobalamin turnover in cats, feline hyperthyroidism may be a risk factor for a functional cobalamin deficiency and a clinical population of cats that may benefit from cobalamin supplementation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have attributed this phenotype to low folate and low creatinine clearance in patients with hypothyroidism, and increased creatinine clearance in patients with hyperthyroidism (Diekman, van der Put, Blom, Tijssen, & Wiersinga, 2001). Demirbas et al have proposed that an increase in creatinine clearance could be the reason for the decrease in plasma homocysteine levels of patients with hyperthyroidism brought to euthyroid status (Demirbas et al, 2004). In our study, the low plasma homocysteine in A-ADHD patients could be due to increased metabolism by hormones, as seen in hyperthyroidism, and therefore increasing glomerular filtration rate thus speeding up homocysteine elimination.…”
Section: Discussionmentioning
confidence: 99%
“…Folat metabolizmasında yer alan MTHFR, MS ve CBS (sistatyon beta sentaz) aktivitelerinin tiroid hormonundan etkilendiği bildirilmektedir. Hipertirodizmde folat düzeyinin yüksek, hipotirodizmde ise düşük olduğu vurgulanmaktadır [37].…”
Section: Tiroidunclassified